A pilot-scale experimental study on MILD combustion of sawdust and residual char solid waste blend using low-temperature preheating air. (15th June 2023) - Hu, Fan; Li, Pengfei; Cheng, Pengfei; Liu, Yaowei; Shi, Guodong; Gao, Yan; Liu, Zhaohui
Highlights: Pilot-test of MILD combustion of solid waste blend is realized for the first time. The burnout rates of solid waste blend MILD combustion are higher than 95%. The fuel-NO emission of MILDC-AS combustion is reduced by 54%. MILD combustion reduces the PM2.5 emissions of biomass blend fuel by 50%. Abstract: The treatment of solid waste through incineration has become an important development trend. A solid waste blend (sawdust and residual char) is studied experimentally in a tubular-furnace reactor and a 200-kW pilot-scale furnace under moderate or intense low-oxygen dilution (MILD) combustion conditions. The effects of temperature and oxygen concentration on NO release characteristics are examined in the tubular-furnace reactor. The pilot-scale furnace experiments include the conventional flame combustion using a swirl nozzle (CFC-S), MILD combustion using symmetrical dual straight nozzles (MILDC-SD), and MILD combustion using an asymmetrical single straight nozzle (MILDC-AS). The tubular-furnace reactor results indicate that the NO released from solid waste blend mainly originates from fuel-NO under medium temperature and low oxygen environments. The pilot-scale furnace results demonstrate that stable combustion of the solid waste blend can be achieved under three co-combustion conditions. Compared to CFC-S, the MILDC-AS combustion of solid waste blend inhibits the fuel-NO and PM2.5 emissions by 54% and 50%, respectively. The burnout rates of solid waste blend MILD combustion exceed 95%. This study not only extends the fuel adaptability of MILD combustion to solid waste blend, but also proves the suppression influence of MILD combustion on fuel nitrogen and PM2.5 emissions.